Gayo Lues Regency Community Perception and Participation in the Implementation of Forest and Land Rehabilitation Activities (RHL) - Iskandar; Orang Kaya Hasnanda Syahputra; Oding Affandi (Talenta Publisher, 2025)
Perceptions and participation of the community must be encouraged cso that forest and land rehabilitation activities become a shared responsibility so that forests do not experience degradation which is very worrying. The purpose of this study is to determine the perception, participation and factors that influence community participation in forest and land rehabilitation activities. The flock that will be conducted research related to Forest and Land Rehabilitation consists of 3 sub-districts namely Terangun, Blangkejeren, and Blangjerango sub-districts of Gayo Lues Regency with a total sample of 91 people. The findings showed that the level of community perception in Terangun, Blangkejeren, and Blangjerango sub-districts on Land and Forest Rehabilitation activities obtained a perception value classified as good in each aspect, namely aspects of planning, implementation, utilization and evaluation. Furthermore, the level of community participation in forest and land rehabilitation (RHL) activities in Terangun, Bangkejeren, and Blangjerango sub-districts can be said to have high participation in each aspect, namely planning, implementation, utilization and evaluation. Then the factors that influence the level of community participation in Land and Forest Rehabilitation activities are age, education level, and income